The Role of Coherence in Text Approaching and Comprehension: Applications in Translation Didactics - Kostopoulou, Georgia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThe communicative text-linguistic approach to the study of texts and their theoretical and methodological problems plays an important role in Translation Studies and in Translation Didactics. The need to use and utilise the textual factors in the translation process and teaching is apparent in various linguistic and translational theories given that Translation, an act of speech and communication, is not performed at the level of language, but at the level of the text and discourse, utilising both linguistic and extralinguistic devices. This paper examines one of the seven textual factors, according to the basic theory of de Beaugrande and Dressler, i.e., the factor of coherence. Given that coherence expresses the logical consistency of utterances in terms of content – and therefore the construction of meaning – concepts such as knowledge, patterns and types of knowledge, frames and scripts, memory, are crucial for describing and examining this factor when approaching and understanding a text. Moreover, the interconnection of text linguistics, translation and cognition is evident, considering de Beaugrande’s argument (1999) that “text linguistics has always had a resolutely cognitive orientation because the text must be described as both product and process.” Furthermore, we shall examine how teachers of translation courses may take into account these concepts and elements when choosing texts for translation purposes, and utilise the theory of high-coherence and low-coherence texts (D. McNamara) in order to assist translator trainees in enhancing their extralinguistic knowledge and in using their prior knowledge during the comprehension/decoding phase of the translation act.